Nesting in Anolis Lizards: An Understudied Topic in a Well-Studied Clade - Pruett, Jenna E.; Hall, Joshua M.; Tiatragul, Sarin; Warner, Daniel A. (Frontiers in Ecology and Evolution, 2022)
Maternal nesting behavior in oviparous species strongly influences the environmental conditions their embryos experience during development. In turn, these early-life conditions have consequences for offspring phenotypes and many fitness components across an individual’s lifespan. Thus, identifying the evolutionary and ecological causes and effects of nesting behavior is a key goal of behavioral ecology. Studies of reptiles have contributed greatly to our understanding of how nesting behavior shapes offspring phenotypes. While some taxonomic groups have been used extensively to provide insights into this important area of biology, many groups remain poorly studied. For example, the squamate genus Anolis has served as a model to study behavior, ecology, and evolution, but research focused on Anolis nesting behavior and developmental plasticity is comparatively scarce. This dearth of empirical research may be attributed to logistical challenges (e.g., difficulty locating nests), biological factors (e.g., their single-egg clutches may hinder some experimental designs), and a historical focus on males in Anolis research. Although there is a gap in the literature concerning Anolis nesting behavior, interest in nesting ecology and developmental plasticity in this group has grown in recent years. In this paper, we 1) review existing studies of anole nesting ecology and developmental plasticity; 2) highlight areas of anole nesting ecology that are currently understudied and discuss how research in these areas can contribute to broader topics (e.g., maternal effects, global change biology); and 3) provide guidelines for studying anole nesting in the field. Overall, this review provides a foundation for establishing anoles as models to study nesting ecology and developmental plasticity.